Narrating the story of a failed national transition: discourses on the Greek crisis, 2010–2014 - Kouki, Hara; Liakos, Antonis (Historein, 2015)
This article traces the construction of the dominant, promemorandum discourse that has been propagated by the political establishment and mainstream media in Greece interpreting the current crisis as a crisis of the national identity: Greece failed to reform where necessary due to the domination of the traditional political culture that is to be blamed for the failed transition since 1974 to postwar European modernity. This narrative is examined within broader narratives and discourses that have attempted in different periods to conceptualise and prescribe the transition to modernity followed not only by Greece, but by other societies the world over. This brief study enables us to think of this exceptional "failed transition" as a not so exceptional or failed transition, while at the same time to observe how societies in crisis turn to history so as to make sense of their present.